2022
DOI: 10.3390/ijerph19020706
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Reconstructed Soil Physicochemical Properties in an Opencast Mine Dump in the Loess Plateau Area of China

Abstract: Soil construction and revegetation are essential for ecological restoration in mining areas. The influence of vegetation on the horizontal and vertical distribution patterns of soil properties should be fully understood. However, most studies on reconstructed soils in mining areas only concentrate on the surface soil, without exploring the vertical variations in soil properties. Overall, this study aims to explore the potential mechanisms by which surface vegetation exerts some influence on the spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In the control (0-NPK) soils, the AC horizon was dominated by subangular structure partially breaking down into granular, while the CA horizon had both subangular and angular. This change in structure from massive (in 1978) to granular/subangular (in 2021) in the surface horizons indicates a major role of plants in the development of pedogenic structure, as also found in other studies [6,12,16,22,40,42,43]. Comparing the structure of Ap1 to the Ap2 subhorizon of fertilized and to the AC horizon of unfertilized soils, it can be concluded that in Ap1, the higher impact of biologic agents and processes on the soil structure transformation was marked, as highlighted by other studies [44,45].…”
Section: Development Of Pedogenic Processessupporting
confidence: 85%
See 1 more Smart Citation
“…In the control (0-NPK) soils, the AC horizon was dominated by subangular structure partially breaking down into granular, while the CA horizon had both subangular and angular. This change in structure from massive (in 1978) to granular/subangular (in 2021) in the surface horizons indicates a major role of plants in the development of pedogenic structure, as also found in other studies [6,12,16,22,40,42,43]. Comparing the structure of Ap1 to the Ap2 subhorizon of fertilized and to the AC horizon of unfertilized soils, it can be concluded that in Ap1, the higher impact of biologic agents and processes on the soil structure transformation was marked, as highlighted by other studies [44,45].…”
Section: Development Of Pedogenic Processessupporting
confidence: 85%
“…This soil take is also connected with opencast mining activities during lignite extraction, as this type of fossil fuel is still an important source of global energy worldwide [3,4]. Poland continues to produce about 28% of its electricity from opencast lignite [5], widely used in many countries around the world [6]. During opencast operations, the natural landscape is damaged along with soils developed over thousands of years and new anthropogenic landforms (e.g., external or internal dumps) with mixed lignite overburden materials are created.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned mine–agriculture–urban compound area is located in Pinglu District, Shuozhou City, Shanxi Province of China (39°21′–39°58′ N, 111°52′–112°41′ E) ( Figure 1 ), which is located in the Loess Plateau hills of north Shanxi Province, where the topography is higher in the northwest than southeast [ 12 , 37 ]. This area is in the northern temperate semi-arid continental monsoon climate zone, where the climate is cold, dry, windy, and sandy with an average annual temperature of 4.50 °C [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…This area is in the northern temperate semi-arid continental monsoon climate zone, where the climate is cold, dry, windy, and sandy with an average annual temperature of 4.50 °C [ 12 ]. The zonal soil type is loessial soil and chestnut soil, and the zonal vegetation type is steppe vegetation [ 12 , 37 , 38 ]. There are many mountains and deep ditches, and there is minimal flat land, serious soil erosion and water loss, low vegetation coverage, and a fragile ecosystem background [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies [46][47][48], the soil physicochemical properties were selected as depicted in Figure 6. The results indicated that apart from SWC, which showed a significant positive response to PV power stations, soil physicochemical properties were not significant.…”
Section: Effects Of Photovoltaic Power Stations On Different Factorsmentioning
confidence: 99%